2015
DOI: 10.1103/physrevc.92.044327
|View full text |Cite
|
Sign up to set email alerts
|

High-spin yrast structure ofHg204from the decay of a four-hole,22+isomer

Abstract: A high-spin isomer with τ > 700 ns has been found in 204

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…It has been demonstrated that experimental energy spectra of several nuclei in the vicinity of 208 Pb are systematically reproduced with the Kuo-Herling interaction and its modified version [63,[66][67][68][69][70][71][72][73]. Those agreements ensure the validity of the effective interaction and the ordering of the lowest two 1 2 − states.…”
Section: Discussionmentioning
confidence: 70%
“…It has been demonstrated that experimental energy spectra of several nuclei in the vicinity of 208 Pb are systematically reproduced with the Kuo-Herling interaction and its modified version [63,[66][67][68][69][70][71][72][73]. Those agreements ensure the validity of the effective interaction and the ordering of the lowest two 1 2 − states.…”
Section: Discussionmentioning
confidence: 70%
“…The conversion coefficient of the 279-keV transition is measured to be 0.2261 (9) [27] and the theoretical value of the same for the 681-keV transition is 0.014 [22]. Using the measured γ -ray intensities, the summed total intensity of the 279-and 681-keV transitions is found to be 108 (5). This value has to be balanced with the summed total intensity of the 328-and 334-keV transitions, allowing for all physically reasonable combinations of multipolarities, along with the inclusion of constraints provided by the data.…”
Section: Resultsmentioning
confidence: 99%
“…This value has to be balanced with the summed total intensity of the 328-and 334-keV transitions, allowing for all physically reasonable combinations of multipolarities, along with the inclusion of constraints provided by the data. The inferred summed total intensity of the 328-and 334-keV transitions using their measured γ -ray intensities (Table I) and theoretical conversion coefficients are (a) 328 (E 1) and 334 (E 3): 107( 5); (b) 328 (M1) and 334 (E 3): 136 (7); and (c) 328 (E 2) and 334 (E 3): 114 (5). Other possible combinations, involving a different multipolarity for either of the two transitions, are quite unlikely based on the data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of metastable states in nuclei with proton or neutron numbers in the vicinity of shell closures is well established as arising from the presence of adjacent excited levels with a relatively large difference in angular momentum and small difference in energy. Isotopes of Hg (Z = 80) and Tl (Z = 81) with A ≈ 200, lying just below the doubly-magic 208 Pb nucleus in the periodic chart, are therefore good candidates for the observation of metastable states or isomers [1][2][3][4][5]. The proton-rich isotopes of Tl (A < 200) are characterized by moderate oblate deformation on account of a significant number of valence neutrons leading to a small degree of collectivity [6,7].…”
Section: Introductionmentioning
confidence: 99%